2010
DOI: 10.1364/oe.18.009815
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and performance criteria of a Stokes polarimeter based on two variable retarders

Abstract: Abstract:In this paper we present the analysis, optimization and implementation of several Stokes polarimeter configurations based on a setup including two variable retarders. The polarimeter analysis is based on the Mueller-Stokes formalism, and as a consequence, it is suitable to deal with depolarized light. Complete Stokes polarimeters are optimized by minimizing the amplification of simulated errors into the final solution. Different indicators useful to achieve this aim, as the condition number or the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 19 publications
3
99
1
1
Order By: Relevance
“…The solid body that is spanned by these four optimal polarization measurements is a tetrahedron, and this construction is widely used with many different implementations. 43,49,50 In general, any modulation cf. an equilateral polygon or Platonic solid inside the Poincaré sphere is optimal with respect to noise propagation to the (fractional) Stokes parameters.…”
Section: Optimizationmentioning
confidence: 99%
“…The solid body that is spanned by these four optimal polarization measurements is a tetrahedron, and this construction is widely used with many different implementations. 43,49,50 In general, any modulation cf. an equilateral polygon or Platonic solid inside the Poincaré sphere is optimal with respect to noise propagation to the (fractional) Stokes parameters.…”
Section: Optimizationmentioning
confidence: 99%
“…Different sets of incident and analyzer SoPs are valid to this aim but the quality of the measurements will depend on different factors, such as the condition number (Taylor, 1974) of the matrices composed by the incident SoPs and the analyzer SoPs (De Martino et al, 2007;Peinado et al, 2010) or the number of SoPs selected (Peinado et al, 2010). Here, the calculation of the Mueller matrix is conducted as follows:…”
Section: Lcos Display Mueller Matrix Characterization: Intensity Predmentioning
confidence: 99%
“…In section 3, we have demonstrated that these small deviations from the theoretical values still result in a well-conditioned system, but an experimental calibration of the matrix to be used for an accurate detection is 06008-p. 5 EPJ Web of Conferences recommended. To this end, we have employed a method based on the one proposed in [14] and described in [7].…”
Section: Calibration and Implementation Of A Stokes Polarimetermentioning
confidence: 99%
“…As a consequence, they are nowadays employed in polarimeter implementations [5][6][7]. Moreover, in order to minimize the amplification of noise (going from radiometric measurements to the state of polarization detection), an optimization procedure is required.…”
Section: Introductionmentioning
confidence: 99%